Determinants of stock market return in Malaysia / Syaidatul Nadia Md Sukor - Md Sukor, Syaidatul Nadia (Faculty of Business and Management, 2014)
The stock market is important resource in the economy of Malaysia. It is difficult to ignore the importance of the stock market return which represents economic activity and initially, stock markets are affected by many highly interrelated economic, political and even psychological factors. Stock market is including in financial market in Malaysia. Financial market plays a crucial role in foundation of a stable and efficient financial system of an economy.